Implementing AMI Network using Riverbed OPNET Modeler for DDoS attack - Bhatt, Tejaskumar; Kotwal, Chetan; Chaubey, Nirbhaykumar (International Journal of Computer Sciences and Engineering, 2019)
Smart meter networks are the spine in distribution grid for smart electrical. Here, in smart Grid, and there are number of smart meters are interconnected and two-way information flows. The distribution side, the smart grid requires the integration of intellectual electronic devices such as Automatic Metering Infrastructure (AMI). This AMI needs wireless communication technology for relay information from the control centre to the energy meters. The flow of information and power in smart grids is bidirectional which is controlled with the help of software and supporting hardware. Optimized Network Engineering Tools (OPNET) Modeler is one of the most dominant simulation tools for the analysis of communication networks. In this paper, a number of models of dissimilar structured smart meter networks were developed with network parameters which were connected with different communication as wired and wireless in which order to compute database query, file transfer to server with respect to time where normal data transfer and DDoS attack to the network. Moreover, a security model that detects the DDoS attacks was mounted on AMI. The outcome of this paper provided a guideline to the future smart meter network developer so as to evade horrible challenges faced by some of the distribution companies. A scenario for the advanced metering infrastructure (AMI), which is one of the smart grid's application areas, was set up and the performance of the test bed was evaluated by implementing an able power management agent model.